Male and Female Differences in Homicide Mortality: Results of an Italian Longitudinal Study, 2012–2018 - Ventura, Martina; Di Napoli, Anteo; Petrelli, Alessio; Pappagallo, Marilena; Mirisola, Concetta; Frova, Luisa (Frontiers in Public Health, 2022)
Introduction: Italy has one of the lowest homicide rates in Europe. However, while it is decreasing overall, the proportion of murdered women is increasing. The aim of this study was to analyse the demographic and socioeconomic characteristics associated with homicide mortality in Italy, focusing specifically on male and female differences. Methods: Using a longitudinal design, the Italian 2011 General Census population was followed up to 2018. Deaths from homicide were retrieved by a record linkage with the Causes of Death Register. Age-standardized mortality rates, stratified by sex, citizenship, education and geographic area of residence, were calculated. The association between sociodemographic characteristics and homicide mortality was evaluated using Quasi-Poisson regression models. Results: Between 2012 and 2018, 1,940 homicides were recorded in Italy: 53% were females over age 55, 10% were immigrant females, 34% were males aged 40–54 years, 76% had a medium-low education level and 57% lived in the South and Islands. Foreign citizenship increased a female’s risk of dying from homicide (RRadj: 1.85; 95% CI: 1.54-2.23), while no differences between Italian and immigrant males were found. An inverse association between education and mortality was observed for both sexes, stronger for males (RRadj: 3.68; 95% CI: 3.10-4.36, low vs high) than for females (RRadj: 1.38; 95%CI:1.17-1.62, low vs high). Moreover, a male residing in the South or in the Islands had almost 2.5 times the risk of dying from homicide than a resident in the North-West. Finally, old age (over 75) increased a female’s risk of being murdered, whereas the highest risk for males was observed for those aged 25–54 years. Conclusions: Male and female differences in homicide mortality profiles by age were expected, but the results by residence, citizenship and education highlight that living in disadvantaged socioeconomic contexts increases the risk of dying from homicide, suggesting the need to implement specific prevention and intervention strategies.